Слепой в зоне: роман / Андрей Воронин - Воронин Андрей (Мартин, 1997)
Экземпляры: ф.7 (2004) / Инвентарный номер: 40006 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: В 75 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44